Management of Tamm–Horsfall Protein for Reliable Urinary Analytics. Issue 6 (8th September 2019) - Xu, Xiaomeng; Barreiro, Karina; Musante, Luca; Kretz, Oliver; Lin, Hanfei; Zou, Hequn; Huber, Tobias B.; Holthofer, Harry
Abstract : Purpose: Urinary extracellular vesicles (uEVs) are a novel source of biomarkers. However, urinary Tamm–Horsfall Protein (THP; uromodulin) interferes with all vesicle isolation attempts, precipitates with normal urinary proteins, thus, representing an unwanted "contaminant" in urinary assays. Thus, the aim is to develop a simple method to manage THP efficiently. Experimental design: The uEVs are isolated by hydrostatic filtration dialysis (HFD) and treated with a defined solution of urea to optimize release of uEVs from sample. Presence of uEVs is confirmed by transmission electron microscopy, Western blotting, and proteomic profiling in MS. Results: Using HFD with urea treatment for uEV isolation reduces sample complexity to a great extent. The novel simplified uEV isolation protocol allows comprehensive vesicle proteomics analysis and should be part of any urine analytics to release all sample constituents from THP trap. Conclusions and clinical relevance: The method brings a quick and easy protocol for THP management during uEV isolation, providing major benefits for comprehensive sample analytics.